First beams from the 1+ source of the ADIGE injector for the SPES Project. Issue 1 (1st April 2022) - Galatà, A; Francescon, P; Roncolato, C; Bisoffi, G; Ballan, M; Bellan, L; Bermudez, J; Bortolato, D; Comunian, M; Conte, A; Lazzari, M De; Fagotti, E; et al.
Abstract: The ADIGE (Acceleratore Di Ioni a Grande carica Esotici) injector consists of an electrostatic 1+ beam line, equipped with ion sources able to produce a wide variety of beams, coupled to a magnetic beam line, where charge multiplication is accomplished by implementing an Electron Cyclotron Resonance (ECR) based charge breeder. The injector is totally integrated in the SPES (Selective Production of Exotic Species) beam line, to allow the post-acceleration of radioactive ions and is now in an advanced phase of installation. The electrostatic 1+beam line has been put into operation and is now producing beams from alkali metals. This contribution concerns the first results of the beam commissioning of this part of the injector, with the description of the initial debug phase and the solutions adopted to ensure a reliable and continuous operation. Preliminary results of the 1+ beam line characterization will be shown, with a comparison between simulated and measured emittances.